2018
DOI: 10.1371/journal.pone.0197687
|View full text |Cite
|
Sign up to set email alerts
|

Selective abdominal venous congestion to investigate cardiorenal interactions in a rat model

Abstract: Abdominal congestion may play an important role in the cardiorenal syndrome and has been demonstrated to drive disease progression. An animal model for abdominal congestion, without other culprit mechanisms that are often present in patients such as low cardiac output or chronic kidney disease, might be interesting to allow a better study of the pathophysiology of the cardiorenal syndrome. The objective of this study was to develop a clinically relevant and valid rat model with abdominal venous congestion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 51 publications
1
28
1
Order By: Relevance
“…The chronic effects of abdominal venous congestion were investigated in this model for a period of 12 weeks. The main findings of this study are that (1) 70] were able to develop a rat model to selectively increase the abdominal venous pressure without compromising cardiac function. These findings exclude the effects of a reduced CO on organ functioning in this rat model.…”
Section: Development Of a New Rat Model Of Abdominal Venous Congestionmentioning
confidence: 96%
See 3 more Smart Citations
“…The chronic effects of abdominal venous congestion were investigated in this model for a period of 12 weeks. The main findings of this study are that (1) 70] were able to develop a rat model to selectively increase the abdominal venous pressure without compromising cardiac function. These findings exclude the effects of a reduced CO on organ functioning in this rat model.…”
Section: Development Of a New Rat Model Of Abdominal Venous Congestionmentioning
confidence: 96%
“…In conclusion, this rat model offers the unique possibility of studying abdominal venous congestion in heart failure and by extension in the cardiorenal syndrome [70,71]. This is important since it remains unclear in which manner venous congestion contributes to cardiac and renal dysfunction in patients, and to develop effective therapeutic strategies in the future.…”
Section: Development Of a New Rat Model Of Abdominal Venous Congestionmentioning
confidence: 98%
See 2 more Smart Citations
“…It remains unclear how isolated venous congestion, separate from cardiac dysfunction, leads to heart and kidney failure in patients 13,14 . However, this can be studied in a rat model with selectively increased abdominal venous pressure, which can be accomplished by permanently constricting the thoracic inferior vena cava (IVC) 15 . It has already been shown that such a model did not compromise cardiac preload or contractile function, while important alterations in kidney morphology and function were observed after twelve weeks 15 .…”
Section: Introductionmentioning
confidence: 99%